Method for producing glass ceramic blank, glass ceramic blank

Through the stacking and pressurized glass ceramic powder, combined with degreasing and impregnation processes, the problem of glass ceramic blanks that are difficult to easily obtain natural tone changes in the prior art is solved, and efficient and natural tone changes are achieved.

CN115835831BActive Publication Date: 2025-03-25GC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280005545.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-10
Publication Date
2025-03-25
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

The prior art is difficult to obtain glass ceramic blanks with natural tone variations easily, and the prior art methods are complex and time-consuming.

Method used

By preparing two or more glass ceramic powders, laminated and press-formed, degreased and immersed in a single color colorant liquid containing metal ions, and finally sintered to obtain a glass ceramic blank with natural tone changes.

Benefits of technology

A simplified process is achieved to efficiently obtain glass ceramic blanks with natural tone variations, with color difference and transmittance differences in conformity with the natural transition of natural teeth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004048896680000111
    Figure BDA0004048896680000111
  • Figure BDA0004048896680000131
    Figure BDA0004048896680000131
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a glass ceramic blank, which includes: preparing two or more glass ceramic powders, stacking the two or more glass ceramic powders in a manner such that adjacent layers have the same color or similar colors and different total light transmittances, and performing press molding; heating the laminate obtained by press molding at a temperature above 500°C and below 800°C for degreasing; immersing the degreased laminate in a single-color colorant liquid containing metal ions in a manner such that the entire laminate is immersed; and heating the laminate immersed in the colorant liquid at a temperature above 750°C and below 1000°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a blank made of glass ceramic before being processed into a dental restoration, in particular to a colored glass ceramic blank. Background Art

[0002] Methods for producing glass ceramic blanks as materials for obtaining dental restorations by cutting include melt molding in which molten glass is poured into a mold and powder molding in which molten lithium silicate glass is crushed and the powder is pressure-molded.

[0003] With the development of digital dentistry in recent years, the demand for all-ceramic restorations has increased, and dental restorations with natural color changes closer to those of natural teeth are required. Therefore, glass ceramic blanks are also required to have natural color changes.

[0004] Melt molding is colored by adding a colorant before melting, so the resulting glass ceramic blank has a single color tone.

[0005] On the other hand, regarding powder molding, Patent Document 1 discloses that powders of different hues are stacked in layers to provide a hue change. In this method, since the layers are stacked, the hue change is prone to have a step difference, and a naturally transitional hue change cannot be obtained.

[0006] In addition, Patent Document 2 discloses that a material obtained by solidifying powder is infiltrated with a plurality of liquids of different colors in a predetermined order. This method requires a plurality of liquids and requires control of the timing and position of infiltration, which is labor-intensive in production.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-68079

[0010] Patent Document 2: Japanese Patent Application Publication No. 2018-15364 Summary of the invention

[0011] Problems to be solved by the invention

[0012] In view of the above problems, an object of the present invention is to provide a method for producing a glass ceramic blank, which can more easily obtain a glass ceramic blank having a natural color tone change. In addition, a glass ceramic blank is provided.

[0013] Methods used to solve problems

[0014] The first embodiment of the present invention is a method for manufacturing a glass ceramic blank, which is a method for manufacturing a glass ceramic blank formed by stacking more than two layers, and includes: preparing two or more glass ceramic powders, and stacking and press-molding the two or more glass ceramic powders in a manner that the colors in adjacent layers are the same or similar and the total light transmittance is different; the step of heating the stacked body obtained by press-molding at a temperature above 500°C and below 800°C for degreasing; the step of immersing the degreased stacked body in a single-color colorant liquid containing metal ions in a manner that the entire stacked body is immersed; and the step of heating the stacked body immersed in the colorant liquid at a temperature above 750°C and below 1000°C.

[0015] In the step of performing press molding in the first aspect, the color difference between adjacent layers may be 5.5 or less.

[0016] In the step of performing press molding in the first aspect, the difference in total light transmittance between adjacent layers may be 0.1% or more and 8% or less.

[0017] In the first aspect, the total light transmittance may be 33% or more.

[0018] A second aspect of the present invention is a glass ceramic blank including two or more layers stacked together, wherein adjacent layers among the two or more layers are made of materials having the same or similar colors and different total light transmittances.

[0019] In the second aspect, between adjacent layers among two or more layers, the color difference of the material constituting the layer itself can be set to 5.5 or less.

[0020] In the second aspect, the difference in total light transmittance may be 0.1% or more and 8% or less.

[0021] In the second aspect, the total light transmittance may be 33% or more.

[0022] Effects of the Invention

[0023] According to the present invention, a glass ceramic raw material having a natural color tone change can be obtained. DETAILED DESCRIPTION

[0024] The method for manufacturing the glass ceramic blank of the present invention is a method of powder molding. That is, molten lithium silicate glass is crushed to obtain powder, and the powder is pressed to mold, thereby obtaining the glass ceramic blank. The details are described below.

[0025] 1. Materials

[0026] When manufacturing the glass ceramic blank of the present invention, the following materials and their amounts are prepared.

[0027] SiO2: 60.0 mass % or more and 80.0 mass % or less

[0028] Li2O: 10.0 mass% or more and 20.0 mass% or less

[0029] Al2O3: 3.0 mass% or more and 15.0 mass% or less

[0030] Here, when SiO2 is out of the above range, it is difficult to obtain a homogeneous glass blank. It is preferably 65 mass % or more and 75 mass % or less.

[0031] When the content of Li2O is outside the above range, it is difficult to obtain a homogeneous glass material. The content of Li2O is preferably 11% by mass or more and 17% by mass or less.

[0032] When Al2O3 is less than 3.0 mass%, although lithium disilicate precipitates as the main crystalline phase, sometimes the machinability becomes problematic, and when it is more than 15.0 mass%, the main crystalline phase is not lithium disilicate, and the mechanical strength may not be satisfactory (for example, lithium aluminosilicate precipitates). Preferably, it is 3.0 mass% or more and 7.0 mass% or less.

[0033] In addition, the material used for the glass ceramic blank may contain the following compound as a crystal nucleus forming material. The material type of the crystal nucleus forming material is not particularly limited, and a wide range of known crystal nucleus forming materials can be used. In this way, crystal nuclei for forming lithium disilicate crystals are efficiently generated.

[0034] Examples of crystal nucleus forming materials include P2O5, TiO2, ZrO2, Ta2O5, ZnO, Nb2O5, Y2O3, La2O3, etc. Such materials may be contained in a range of 0 mass % or more and 10.0 mass % or less. As shown in the composition shown here, 0 mass % is included, and it is also known that they do not necessarily need to be contained, and any one of them may be contained. The same applies to the following.

[0035] Furthermore, the material of the glass ceramic raw material may contain the following components in addition to the above. Each of them may be contained in an amount of 0 mass % or more and 15 mass %, but the following are more preferable.

[0036] Na2O: 0 mass% or more and 2.8 mass% or less

[0037] K2O: 0 mass% or more and 10.0 mass% or less

[0038] CaO: 0 mass% or more and 3.0 mass% or less

[0039] SrO: 0 mass% or more and 10.0 mass% or less

[0040] BaO: 0 mass% or more and 10.0 mass% or less

[0041] MgO: 0 mass% or more and 3.0 mass% or less

[0042] Rb2O: 0 mass% or more and 2.8 mass% or less

[0043] Cs2O: 0 mass% or more and 2.8 mass% or less

[0044] Fr2O: 0 mass% or more and 2.8 mass% or less

[0045] BeO: 0 mass% or more and 3.0 mass% or less

[0046] RaO: 0 mass% or more and 10.0 mass% or less

[0047] These components can adjust the melting temperature of the material when producing the dental restoration material. However, even if more of these components are contained, the improvement of the effect is limited, so even if contained, it can be set to 15% by mass or less as described above.

[0048] In addition, from the viewpoint of adjusting light transmittance, at least one selected from CeO2, Er2O3 and Tb4O7 may be contained. When contained, the content may be set to about 1 mass % or less.

[0049] 2. Method for manufacturing glass ceramic blank

[0050] Hereinafter, a method for manufacturing a glass ceramic blank of one embodiment will be described. The manufacturing method S10 of the glass ceramic blank of this embodiment (hereinafter sometimes referred to as "manufacturing method S10") comprises: a step of preparing two or more powder materials (step S11), a step of making a pressurized laminate (step S12), a step of degreasing treatment (step S13), a step of immersing in a colorant liquid (step S14), and a step of sintering (step S15). Hereinafter, each step will be described.

[0051] 2.1. Preparing two or more powder materials (step S11)

[0052] In step S11, two or more powder materials having characteristics in color and light transmittance are prepared based on the above-mentioned materials. Various powder materials can be obtained by blending the above-mentioned materials, melting them at a temperature of 1300°C or higher and 1600°C or lower, and then pulverizing them after cooling and solidifying. The pulverization method and the degree of pulverization are well known, and for example, a range in which the particle size of the powder is 10 μm or higher and 60 μm or lower can be cited. Here, "particle size" refers to the particle size (D50) when the cumulative value is 50% in the volume-based particle size distribution measured by a laser diffraction / scattering method.

[0053] The characteristics of color and light transmittance of the prepared two or more powder materials are as follows.

[0054] [About color]

[0055] The two or more prepared powder materials have the same or similar colors when adjacently stacked in step S12. Specifically, the color difference ΔE between the two or more prepared powder materials when adjacently stacked in step S12 is preferably 5.5 or less.

[0056] Here, the color difference ΔE refers to "L * a * b * Color difference ΔE in color space * ab ". That is, the L of two adjacent layers * a * b * The distance between the colors in the color space is ΔE, and the colors of the two layers are set to (L * 1.a * 1. b * 1) (L * 2.a * 2. b * 2), it is expressed by the following formula.

[0057] ΔE={(L * 2-L * 1) 2 +(a * 2-a * 1) 2 +(b * 2-b * 1) 2} 0.5

[0058] The color difference ΔE was measured as follows.

[0059] Each powder used is molded into a cylindrical shape, and then the same degreasing process as step S13 and sintering process S15 are carried out to prepare a color plate (without coloring in step S14), and a shape with a thickness of 1.2 mm is formed using #1000 waterproof sandpaper. That is, the color difference ΔE mentioned here refers to the color difference of the color plate obtained by molding each powder into a cylindrical shape without coloring and performing the same heat treatment as step S13 and sintering in step S15, and refers to the difference in color tone of the powder material itself (distinguished from the color difference after coloring in step S14 shown later).

[0060] Then, the color of the sample was measured using a spectrocolorimeter (SD7000: manufactured by NIPPON DENSHOKU). The obtained color coordinates (CIE 1976 L according to JIS Z 8781-4) were used. * a * b * The color difference ΔE is calculated by the above formula.

[0061] [About light transmittance]

[0062] The two or more prepared powder materials have different light transmittances. Specifically, among the two or more powder materials, the total light transmittances are different between the powder materials stacked adjacent to each other in step S12.

[0063] The total light transmittance is measured using a haze meter (NDH5000 (manufactured by NIPPON DENSHOKU) by a method in accordance with JIS K 7361, using CIE standard illuminant D65 as incident light, and can be defined as the sum of the diffuse transmittance and the linear transmittance of the incident light.

[0064] In the present invention, as in the case of measuring color difference, each powder used is molded into a cylindrical shape, and then the same degreasing as in step S13 and sintering as in step S15 are performed to prepare a color plate (without coloring in step S14), and a shape with a thickness of 1.2 mm is formed using #1000 waterproof sandpaper, and the total light transmittance obtained for the material thus prepared is used. That is, the total light transmittance mentioned here is the total light transmittance of the color plate obtained by molding each powder into a cylindrical shape and then performing the same heat treatment as in step S13 and sintering in step S15 without coloring, and is a value based on the total light transmittance of the powder material itself.

[0065] The difference in total light transmittance between the types of powder materials in adjacent layers is not particularly limited, but is preferably 0.1% to 8%, more preferably 0.1% to 6%, and even more preferably 0.1% to 3%.

[0066] The total light transmittance of the two or more powder materials is not particularly limited, but preferably at least one of them is 33% or more, and more preferably all of them are 33% or more.

[0067] 2.2. Preparation of Pressurized Laminated Body (Step S12)

[0068] In step S12, the two or more powder materials obtained in step S11 are sequentially stacked in a mold and pressure-molded to obtain a pressurized stack.

[0069] More specifically, the process is performed by mixing the respective powder materials with a resin as a binder, sequentially stacking the mixture in a mold, and then applying pressure.

[0070] The binder is not particularly limited as long as it is a resin that burns out by heating at 500° C. to 800° C., and for example, an acrylic resin is preferred. In the present embodiment, Oricox KC-1700P (Kyoeisha Chemical Co., Ltd.) is used.

[0071] The pressurization can be performed, for example, by a uniaxial press, at a pressure of 10 MPa or more and less than 20 MPa, preferably 10 MPa or more and 18 MPa or less.

[0072] 2.3. Degreasing treatment (step S13)

[0073] In step S13, the pressurized laminate obtained in step S12 is heated to remove the binder resin contained in the pressurized laminate (degreasing). The heating temperature is not particularly limited, but is preferably about 500° C. or more and about 800° C. or less. Among them, since crystallization of lithium metasilicate begins at 680° C., heating to about 700° C. is more preferred from the viewpoint of smoothly proceeding the crystallization.

[0074] 2.4. Immersing in Colorant Liquid (Step S14)

[0075] In step S14, the degreased pressurized laminate obtained in step S13 is immersed in a colorant liquid to obtain a colored pressurized laminate.

[0076] Here, the colorant liquid may be a single color, and for example, a colorant obtained by mixing metal ions as a colorant with a solvent may be mentioned.

[0077] The solvent is not particularly limited as long as it can dissolve the colorant, and examples thereof include distilled water and alcohol (methanol, ethanol), and the like.

[0078] The colorant can be any suitable metal ion, for example, metal ions contained in metal oxides that can be used as colorants in lithium silicate glass ceramics. More specifically, salts containing metals such as Ce, Er, Fe, Mn, Tb, and V can be cited, such as erbium acetate and cerium acetate.

[0079] Furthermore, polyethylene glycol, polypropylene glycol, etc. may be contained as a permeability regulator to improve the permeability to the degreased pressurized laminate as needed. In addition, a trace amount of hydrochloric acid may be contained. Thus, it becomes easy to dissolve the metal salt in the solvent.

[0080] The content is not particularly limited, and for example, the solvent may be 70% to 90% by mass, the colorant may be 0.1% to 20% by mass, and the permeability regulator may be 0% to 15% by mass.

[0081] The infiltration is preferably performed by immersing the entire degreased pressurized laminate in the colorant solution. The immersion can be performed at an ambient temperature, preferably in a range of 10° C. to 40° C. In addition, the immersion time is preferably 1 minute or more. The upper limit of the immersion time is not particularly limited, but is preferably 60 minutes or less. This is because even if the immersion time exceeds the above time, there is almost no effect on the result.

[0082] 2.5. Sintering (Step S15)

[0083] In step S15, the colored pressurized laminate obtained in step S14 is subjected to a heat treatment to be sintered and then cooled to obtain a glass ceramic green body.

[0084] The heat treatment is maintained at a temperature higher than 750° C. and lower than 1000° C. for a predetermined time. As a result, crystals of lithium disilicate grow, and a lithium disilicate blank having lithium disilicate as the main crystal phase can be obtained. The maintenance time is preferably 1 minute or more, more preferably 3 minutes or more. The upper limit of the time is not particularly limited, and can be set to 3 hours or less.

[0085] 3. Glass ceramic blanks

[0086] The glass ceramic blank obtained by the manufacturing method S10 is a block-shaped raw material in the shape of a column such as a prism or a cylinder, or a plate such as a square plate or a circular plate. The block-shaped raw material can be deformed and cut by mechanical processing such as cutting to produce a dental restoration.

[0087] In addition, the color difference between adjacent layers of the obtained glass ceramic blank is preferably 8 or less, and the total light transmittance is also preferably different. It should be noted that, as described above, the color difference between adjacent layers in the obtained glass ceramic blank is different from the color difference of the powder material.

[0088] Furthermore, it is preferred that the coloring agent contained in the glass ceramic raw material be of the same type and concentration in any part.

[0089] 4. Effects, etc.

[0090] According to the method for producing a glass ceramic blank described above, a glass ceramic blank having a natural color change like a natural tooth can be efficiently produced simply by immersing the blank in a coloring agent liquid of a single color.

[0091] In addition, by using a material satisfying the above-described color and light transmittance between adjacent layers, a glass ceramic blank having a natural color change like natural teeth can be produced.

[0092] In the powder material used, by setting the difference in total light transmittance between materials constituting adjacent layers to be 0.1% or more and 8% or less, the change in color tone between the layers can be perceived more naturally.

[0093] Furthermore, by setting the total light transmittance of at least one, more preferably all, of the powder materials to be 33% or more, the color tone change between the layers can be felt more naturally. In addition, the coloring in step S14 can be performed more smoothly.

[0094] 5. Examples

[0095] In the examples, two or more types of powders (powder A to powder J) having different characteristics were used and combined to produce glass ceramic blanks, and tests were performed.

[0096] 5.1. Preparation of powder

[0097] The powders prepared in step S11 are shown in Table 1. Table 1 also shows the color and the total light transmittance measured by the above-mentioned method for each powder.

[0098] The composition of each powder was changed within the following range.

[0099] SiO2: 69.8 mass % or more and 71.2 mass % or less

[0100] Li2O: 11.2 mass% or more and 13.5 mass% or less

[0101] Al2O3: 4.3 mass% or more and 5.3 mass% or less

[0102] P2O5: 3.0 mass% or more and 7.3 mass% or less

[0103] Na2O: 1.2 mass% or more and 1.6 mass% or less

[0104] K2O: 1.8 mass% or more and 2.4 mass% or less

[0105] SrO: 0 mass% or more and 1.7 mass% or less

[0106] TiO2: 0 mass% or more and 0.5 mass% or less

[0107] ZrO2: 1.8 mass% or more and 3.2 mass% or less

[0108] CeO2: 0.1 mass% or more and 0.2 mass% or less

[0109] Tb4O7: 0.4 mass%

[0110] Colorant: Powder H, Powder I and Powder J only 0.2 mass%

[0111] The various types of powder materials were obtained by mixing the above materials, melting them at 1300° C. to 1600° C., cooling and solidifying them, and then pulverizing them to obtain the various types of powder materials. The particle size of the obtained powder was 36.53 μm in terms of D50.

[0112] [Table 1]

[0113] (Table 1)

[0114]

[0115] Here, the color A1 of the powder H, the color B1 of the powder I, and the color A2 of the powder J are named based on color samples in the VITA Classical Shade Guide (manufactured by VITA).

[0116] 5.2. Preparation of glass ceramic blanks

[0117] The prepared powders are made into a layer structure of the combination shown in Table 2 (for example, "A+B" means a layer formed by powder A and a layer formed by powder B are stacked), and a glass ceramic blank is produced according to steps S12 to S14. The conditions of each step are as follows.

[0118] In the step S12, Oricox KC-1700P (Kyoeisha Chemical Co., Ltd.) was used as a binder and mixed in an amount of 5 mass % relative to the powder material. Then, the mixture was pressed with a uniaxial press at a pressure of 15 MPa.

[0119] In the step S13 , the obtained pressurized laminate is heated at 700° C. for 10 hours to perform degreasing.

[0120] In the step S14, the degreased pressurized laminate is immersed in a coloring agent liquid at 23°C (room temperature) for 10 minutes. The composition of the coloring agent liquid is as follows.

[0121] Cerium acetate: 6.5 mass%

[0122] Erbium acetate: 6.5 mass%

[0123] Polyethylene glycol: 7.0 mass%

[0124] Distilled water: 80% by mass

[0125] In the step S15 , the pressurized laminated body immersed in the coloring agent liquid is heated at 880° C. for 1 hour to be sintered.

[0126] 5.3. Evaluation and results

[0127] Evaluation items and results are shown in Table 2. Each item is as follows.

[0128] [Color difference ΔE]

[0129] The color difference ΔE between adjacent layers of the prepared powder material itself is measured by the above method.

[0130] [Total light transmittance difference]

[0131] Based on the total light transmittance of each powder material itself in Table 1, the difference (%) between the total light transmittances of adjacent layers in each combination was calculated.

[0132] [Sensory evaluation (transitional)]

[0133] The sensory evaluation was conducted for natural color tone changes. The evaluation was conducted visually by 5 people, and the number of people who felt that the color tone changes were natural was used as the evaluation standard. Specifically, the case where the number of people who felt that the color tone changes were natural was set as "excellent", the case where the number of people who felt that the color tone changes were natural was set as "good", the case where the number of people who felt that the color tone changes were natural was set as "pass", and the case where the number of people who felt that the color tone changes were natural was set as "fail".

[0134]

[0135] As can be seen from Table 2, by setting the color difference ΔE between adjacent layers in the prepared powder material to 5.5 or less, a glass ceramic green body having a natural color tone change can be obtained.

[0136] It should be noted that, as in Example 10, when the prepared powder materials each having a total light transmittance of less than 33% are combined, the transition property is slightly reduced. In addition, in this case, coloring takes time and the coloring efficiency tends to be reduced.

Claims

1. A method for manufacturing a glass ceramic blank, which is a method for manufacturing a glass ceramic blank formed by stacking two or more layers, comprising: A step of preparing two or more glass ceramic powders, laminating the two or more glass ceramic powders so that the color difference between adjacent layers is 5.5 or less and the total light transmittance is different, and performing pressure molding; The step of heating the laminate obtained by the press molding at 500° C. to 800° C. to degrease the laminate; A step of immersing the degreased laminate in a single-color colorant liquid containing metal ions so that the entire laminate is immersed; as well as The step of heating the laminated body immersed in the colorant liquid at a temperature higher than 750° C. and lower than 1000° C., The color difference is the color difference of a color palette obtained by molding each of the powders into a cylindrical shape with a thickness of 1.2 mm, then performing degreasing and heat treatment without coloring. The total light transmittance is the total light transmittance of a color plate obtained by molding each of the powders into a cylindrical shape with a thickness of 1.2 mm and then performing degreasing and heat treatment without coloring.

2. The method for producing a glass ceramic blank according to claim 1, wherein: In the step of press-molding, a difference in the total light transmittance between the adjacent layers is 0.1% or more and 8% or less.

3. The method for producing a glass ceramic blank according to claim 1 or 2, wherein: The total light transmittance is greater than 33%.

4. A glass ceramic blank obtained by the method for producing a glass ceramic blank according to any one of claims 1 to 3, wherein the glass ceramic blank is a glass ceramic blank formed by laminating two or more layers, wherein: Adjacent layers among the two or more layers have a color difference of 5.5 or less in color of the material constituting the layer itself and different total light transmittances.

5. The glass-ceramic blank according to claim 4, wherein: The difference in total light transmittance is greater than or equal to 0.1% and less than or equal to 8%.

6. The glass ceramic blank according to claim 4 or 5, wherein: The total light transmittance is greater than 33%.

Citation Information

Patent Citations

  • Multi-colored shaped body

    JP2008068079A

  • Dental tentative calcined body with colored inside

    JP2018015364A

  • Multi-colored shaped body

    US20080064011A1